Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Postharvest control of Botryosphaeria dothidea-induced pear ring rot by Chrysanthemum indicum essential oil: Composition, efficacy, and mechanistic insights - Bin Wang; Sha-Sha Liu; Jia-Ying Wu; Meng-Ran Yu; Yun-Kai Lv; Jian Wang; Li-Juan Wang; Fei Cao (Postharvest Biology and Technology, 2026)

Hierarchical metal-organic frameworks and biomass-derived nanocellulose as dual enzyme carriers: Construction of a modular, tunable enzyme-membrane reactor for the efficient degradation of phenol - Guiru Chen; Hongyu Wang; Ran Song; Fei Wang; Yuting Ren; Chunlin Huang; Xuyue Dou; Jiandu Lei; Luying Wang (Bioresource Technology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Climate value of energy storage for floating photovoltaic across China’s decarbonizing power grids - Ran Hao; Xin Sun; Yuchen Zhao; Chengchao Huang; Lili Yang; Weiqiao Wang; Junyu Sun; Li Fei; Lihao Zhao (ENGINEERING Environment, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Carboxymethyl cellulose-metal organic frameworks composites: From synthesis to applications - Hongyu Wang; Ran Song; Guiru Chen; Fei Wang; Luying Wang; Jing Liu; Jiandu Lei (Carbohydrate Polymers, 2026)

CNF-stabilized liquid metal reinforced dual-network anti-freezing hydrogel for multifunctional wearable bioelectronics - Hongyu Wang; Guiru Chen; Ran Song; Fei Wang; Luying Wang; Jing Liu; Jiandu Lei (Chemical Engineering Journal, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Direct synthesis of non-migratory, intrinsically antioxidant ultra-high molecular weight polyethylene by nickel catalysis - Fei-Ran Yang; Wen-Bing Wang; Tian-Ming Yang; Hao-Xiang Sun; Quan Wang; Meng-He Xu; Jia-Wei Chen; Chen Zou (Chemical Engineering Journal, 2026)

Soil quality evaluation of no-tillage reseeding grassland based on quality index area and sensitivity-resistance method - Xiaoqing Qiu; Shuang Yan; Hao Shi; Fei Xia; Wei Wei; Yu Zhang; Jiarui Ding; Jiayu Cao; Haoyang Wu; Linling Ran; Jinglong Wang; Junqiang Wang (Applied Soil Ecology, 2026)

Intraseasonal variability and eddy-induced structural modulation of the North Pacific intermediate water revealed by multi-mooring observations - Qiang Ren; Yansong Liu; Yansheng Zhang; Shumin Tu; Wei Huang; Feng Nan; Ran Wang; Xinyuan Diao; Jianfeng Wang; Xinchuang Liu; Zifei Chen; Fei Yu (Ocean Science, 2026)
The North Pacific Intermediate Water (NPIW) plays an important role in regulating thermohaline structure and biogeochemical distributions in the North Pacific. However, limited continuous observations have hindered our understanding of its short-term variability and structural response to mesoscale processes. Based on 1 year mooring observations from three sites (M1–M3) in the western North Pacific, this study investigates the intraseasonal structural variability of the NPIW and its modulation by mesoscale eddies. The NPIW thickness exhibits pronounced intraseasonal variability, with a dominant period of approximately 60–80 d that is coherent among the three mooring sites. Unlike previous studies that mainly focused on temperature and salinity anomalies, this study introduces NPIW thickness as a structural diagnostic parameter to characterize the vertical compression and expansion of the intermediate layer associated with mesoscale variability. The results reveal a clear inverse relationship between NPIW thickness and salinity, indicating that anticyclonic conditions are generally associated with thinner and more saline intermediate layers, whereas cyclonic conditions correspond to thicker and relatively fresher layers. Spatial composite analyses further show that thickness and salinity responses exhibit clear regional differences, with stronger variability near the western boundary, likely related to complex water-mass redistribution and possible mixing processes. These findings provide quantitative observational evidence for intraseasonal variability in NPIW thickness and highlight its usefulness as a diagnostic indicator for mesoscale–intermediate water interactions in the North Pacific.

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

A biomass-derived modular hydrogel platform for multimodal physical, chemical, and biological sensing - Hongyu Wang; Guiru Chen; Ran Song; Fei Wang; Luying Wang; Jing Liu; Jiandu Lei (Chemical Engineering Journal, 2026)

Physical and biological synergistic strategies: injectable CNF/CMC hydrogels with cannabidiol@PCL microspheres for durable facial filling - Hongyu Wang; Guiru Chen; Ran Song; Fei Wang; Yunjian Chen; Luying Wang; Jiandu Lei; Jing Liu (Carbohydrate Polymers, 2026)

Algal community composition drives lake greenhouse gas emissions via dissolved organic matter transformation and microbial processing - Weiqiao Wang; Xin Sun; Ran Hao; Fei Li (Journal of Environmental Management, 2026)

Quantity and quality decoupling in soil carbon sequestration: A case study focusing on the stability of soil organic matter in reclaimed coal gangue soils - Fei Wang; Ran Zhao; Kang Zhao; Yi-Zong Huang; Feng Xu (Journal of Environmental Sciences, 2026)

Recent advances in the design mechanisms of mitochondrial fluorescent probes: A review - Fei Peng; Bo Wang; Yunjia Xu; Ran Chai; Aibing Wu; Mingming Xue; Huijuan Tian; Yan Lv; Xiangyu Guo; Bin Hao; Baoxiang Gao (Analytica Chimica Acta, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Sustainable management of plateau mountainous urban agglomerations based on the ecosystem services supply-demand balance: Application of scale and threshold effects - Xiaobao Wang; Xiaoqing Zhao; Yuju Ran; Yanmin Fan; Wentao Li; Xianmin Ye; Yuqin Zhou; Yanlin Wang; Fei Liu (Journal of Cleaner Production, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Source, bioaccessibility and oral exposure risk assessment of rare earth elements in soils with typical land-use types - Liwen Zhang; Xiaoli Duan; Ran Li; Wenyu Wu; Fei Gao; Hongguang Cheng; Beibei Wang (Journal of Environmental Sciences, 2026)

Designing dual vacancies sites in VS₄-ZnZrOx/SAPO-34 tandem catalyst for enhanced CO2 hydrogenation performance - Xinyi Ran; Fei Liu; Shangyan Zhou; Huayuying Peng; Xiaodan Wang; Mengqin Yao (Chemical Engineering Journal, 2026)

Carboxymethyl cellulose hydrogels for flexible electronics: From design to applications - Hongyu Wang; Ran Song; Guiru Chen; Fei Wang; Luying Wang; Jiandu Lei; Jing Liu (Carbohydrate Polymers, 2026)

A provenance study of turquoise artifacts at the Sanxingdui site in Sichuan, China - Zeya Shang; Jianfeng Cui; Honglin Ran; Chong Wang; Zhenbin Xie; Yu Lei; Fei Tang; Dengyi Zhang; Haichao Li (Archaeological and Anthropological Sciences, 2026)

Construction of CeO2/Bi2O3 heterojunction photocatalyst for the efficient degradation of organic dyes - Shen Hu; Qingyao Wang; Xu Gao; Shuaiqi Ren; Xiaoru Li; Ran Geng; Mengxiang Lei; Chunyan Zhang; Fan Fei; Kesheng Wang (Fuel, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Biomass-based dual-network multifunctional hydrogel for durable wearable sensors and emergency hemostasis - Hongyu Wang; Ran Song; Guiru Chen; Fei Wang; Luying Wang; Jiandu Lei; Jing Liu (Chemical Engineering Journal, 2026)

An optimal method for GNSS water vapor tomography based on parameter adaptation - Fei Yang; Ruixian Hao; Haoyu Wang; Lei Wang; Zhicai Li; Junxi Zheng; Yingying Wang; Ran Chen (GPS Solutions, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Contribution of lakes to global greenhouse gas emissions: Mechanisms, quantification and mitigation strategies - Weiqiao Wang; Xin Sun; Xue Zhu; Ran Hao; Fei Li (Journal of Environmental Management, 2026)

Dual-interface MXene engineering for low-noise perovskite photodetectors in optical communication and health monitoring - Shareen Shafique; Haodong Wang; Yegang Lu; Taimoor Iqbal; Yuheng Wang; Baihui Shen; Ran Zhao; Li Sheng; Cheng Yang; Muhammad Sulaman; Fei Zheng; Ziyang Hu (Chemical Engineering Journal, 2026)

HPLC-UV guided isolation of anti-inflammatory polyacetylene glucosides from Carthamus tinctorius L. - Yong-Xiang Wang; Jia-Xu Bao; Ran Wang; Xian Zhang; Yun-Fang Zhao; Peng-Fei Tu; Hui-Xia Huo; Jun Li (Phytochemistry, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

The effect of degree of esterification of pectin on the grainy properties of post-heated fermented milk - Fei Gao; XueYing Mao; Pengjie Wang; Ran Wang; Hongliang Li; Hairan Ma; Chong Chen; Sijia Song; Dongdong Li (Food Hydrocolloids, 2025)

A HOF-COF hybrid photocatalyst for sacrificial agent-free uranium extraction via photogenerated-H2O2-mediated precipitation - Fei Han; Qiyue Zhang; Xia Wang; Wei Liu; Ran Jia; Xiaomei Wang; Zhongyue Li (Chemical Engineering Journal, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Efficient mining of natural products from Mangrove streptomyces using NP-PRESS - Lin Yu; Junxiao Wang; Kai Jin; Fan Xu; Yi Huang; Ran Zhang; Yihan Wu; Fei Xu (Archives of Microbiology, 2025)

Soil health assessment of urban forests in Nanchang, China: Establishing a minimum data set model - Fei Huang; Jiamei Tu; Foyi Zhang; Jingwang Ran; Yi Wang; Wei Liu; Wenxuan Chen; Xinyao Wang; Qiong Wang (Soil Biology and Biochemistry, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Macrophage membrane-based biomimetic nanocarrier system for enhanced immune activation and combination therapy in liver cancer - Wei Ni; Mingzhu Zhang; Yueni Mo; Wei Du; Hui Liu; Zhaosong Wang; Yanfen Cui; He Zhang; Zhiyong Wang; Liming Liu; Hui Guo; Ruifang Niu; et al. (Drug Delivery and Translational Research, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Impact of net-zero emissions on atmospheric CO2 concentration in China: Ideal simulations based on the GEOS-Chem model - Jingye Tan; Jun Wang; Huiqin Mao; Hengmao Wang; Zhiqiang Liu; Meirong Wang; Ran Yan; Xunmei Wang; Fei Jiang (Science China Earth Sciences, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Coalescence characteristics of free-living and particle-attached bacteria in a cascade river-reservoir system: A case study of the Jinsha River - Dan Zhang; Yufei Bao; Yuchun Wang; Jingjie Feng; Ran Li; Yanliang Du; Dianchang Wang; Fei Chen; Shanze Li; Jie Wen; Zhuo Chen (Journal of Environmental Management, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Research on the source of cinnabar excavated from Sanxingdui site in China based on sulphur and mercury isotope analyses - Qinxin Jiang; Guangyi Sun; Honglin Ran; Yu Lei; Chong Wang; Zhenbin Xie; Fei Tang; Jian Yu; Bisu Zhou; Min Shi; Wan Peng; Chenghui Li; et al. (Archaeological and Anthropological Sciences, 2025)

Dual-ion permeation Janus membrane-assisted element reconstitution system enables fluorosilicate-oriented recovery from fluoride-rich and silica-rich wastewaters - Yangbo Qiu; Chao Wang; Ran Li; Lidong Feng; Shuaijun Yu; Jiangnan Shen; Long-Fei Ren; Jiahui Shao (Water Research, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

A novel dual-emission fluorescence sensor with different responsive modes for non-invasive and simultaneous quantitative detection of carbaryl and imidacloprid - Yi-Fan Xia; Hou-Qun Yuan; Zhi-Qiang Cai; Le Fang; Zhen-Chong Dou; Qian-Wen Yang; Yi-Xuan Hu; Ran Wang; Yu-Fei Zhong; Guang-Ming Bao (Chemical Engineering Journal, 2025)

An active-conductive layer stacked sensor platform for real-time detection of heavy metal ions - Yuping Yang; Lijia Xu; Yongpeng Zhao; Yuchao Wang; Zhijun Wu; Zhiliang Kang; Zhiyong Zou; Hui Huang; Yong He; Fei Liu; Zuoliang Tang; Ao Feng; et al. (Chemical Engineering Journal, 2025)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Influence of extreme 2022 heatwave on megacities' anthropogenic CO2 emissions in lower-middle reaches of the Yangtze River - Jingye Tan; Jun Wang; Haikun Wang; Zhu Liu; Ning Zeng; Ran Yan; Xinyu Dou; Xunmei Wang; Meirong Wang; Fei Jiang; Hengmao Wang; Weimin Ju; et al. (Science of The Total Environment, 2024)

Impacts of nano- and micro-plastics exposure on zooplankton grazing, bacterial communities, and dimethylated sulfur compounds production in the microcosms - Yu Jiang; Juan Yu; Rong Chen; Su Wang; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song (Environmental Pollution, 2024)

Novel visible-light activated photocatalytic ultrafiltration membrane for simultaneous separation and degradation of emerging contaminants - Ran Li; Zhidong Wei; Peng Li; Yangbo Qiu; Chengyi Wang; Chao Wang; Long-Fei Ren; Jiahui Shao; Yiliang He (Journal of Hazardous Materials, 2024)

Visual environment in schools and student depressive symptoms: Insights from a prospective study across multiple cities in eastern China - Xiyan Zhang; Jiawen Tang; Yan Wang; Wenyi Yang; Xin Wang; Ran Zhang; Jie Yang; Wei Lu; Fei Wang (Environmental Research, 2024)

Patterns and drivers of organic carbon in hydromorphic soils across inland aquatic-terrestrial ecotones at the global scale - Yiguo Ran; Peng Wang; Fei Ye; Junfeng Qu; Yang Ning; Yanshuo Zhang; Zhaofei Wen; Shengjun Wu; Ping Huang (CATENA, 2024)

Conservation tillage as an economic and ecological farming option for Summer Maize in the oasis region of Northwest China - Yunyin Xue; Juanjuan Zhou; Linling Ran; Haoyang Wu; Wei Wei; Xinkun Hu; Fei Xia; Junqiang Wang (Plant and Soil, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Novel electrocatalytic capacitive deionization with catalytic electrodes for selective phosphonate degradation: Performance and mechanism - Chengyi Wang; Siyue Xue; Yubo Xu; Ran Li; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Water Research, 2024)

Effects of micro- and nano-plastics on growth, antioxidant system, DMS, and DMSP production in Emiliania huxleyi - Juan Yu; Ji-Yuan Tian; Yu Jiang; Xue-Dan Wang; Xin-Ran Song; Long-Fei Liu; Gui-Peng Yang (Environmental Pollution, 2024)

Maize Straw and Nitrogen Fertilizer Alter Soil Carbon and Nitrogen Mineralization during the Fallow Period in the Oasis Farmland area - Yunyin Xue; Fei Xia; Linling Ran; Youlong Xu; Haoyang Wu; Wei Wei; Zhiguo Shi; Xiaobing Cai; Junqiang Wang (Journal of Soil Science and Plant Nutrition, 2024)

Intraseasonal variability of the deep scattering layer induced by mesoscale eddy - Bei Wang; Fei Yu; Ran Wang; Zhencheng Tao; Qiang Ren; Xing Chuan Liu; Jian Feng Wang (Frontiers in Marine Science, 2024)
The deep scattering layer (DSL), a stratum of the marine diel vertical migration (DVM) organisms inhabiting the mesopelagic ocean, plays a crucial role in transporting carbon and nutrients from the surface to depth through the migration of its organisms. Using 18 months of in-situ observations and altimeter sea level data, we reveal for the first time the intraseasonal variations and underlying mechanisms of the DSL and the DVM to the east of the Taiwan Island. Substantial vertical speeds acquired from the Acoustic Doppler Current Profiler were used to examine the distribution and variation of the DVM. Innovatively, the results for the power spectrum analysis of the scattering intensity demonstrated a significant intraseasonal variability (ISV) with an 80-day period in the DSL. Furthermore, the variation in the DVM was closely linked to the DSL and showed an 80-day ISV during the observation. A dynamic relationship between the ISV of the DSL east of Taiwan Island and the westward-propagating mesoscale eddies was established. Anticyclonic (cyclonic) eddy movement toward Taiwan Island triggers downward (upward) bending of the local isotherms, resulting in a layer of DSL warming (cooling) and subsequent upper boundary layer deepening (rising). These findings underscore the substantial influence of mesoscale eddies on biological activity in the mesopelagic ocean, establishing a novel understanding of ISV dynamics in the DSL and their links to eddy-induced processes.

Ecoregion-wise fractional mapping of tree functional composition in temperate mixed forests with sentinel data: Integrating time-series spectral and radar data - Ziyu Lin; K.H. Cheng; Dedi Yang; Fei Xu; Guangqin Song; Ran Meng; Jing Wang; Xiaolin Zhu; Michael Ng; Jin Wu (Remote Sensing of Environment, 2024)

Spatiotemporal distribution and impact factors of GNSS-PWV in China based on climate region - Fei Yang; Xu Gong; Zhicai Li; Yingying Wang; Shiji Song; Haoyu Wang; Ran Chen (Advances in Space Research, 2024)

Petrogenesis of the late Cenozoic potassium-rich volcanism in the NW Tibetan Plateau: Constraints on the mantle evolution through post-orogenic events - Masumeh Sargazi; Chuan-Lin Zhang; Zhi-Hao Song; Hong-Ran Wang; Zahid Hussain; Xian-Tao Ye; Wei Wang; Xiao-Fei Du (Lithos, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Defect-promoted nanoparticles−nanorod Ni−NiMoO4 heterogeneous nanostructures as efficient electrocatalysts to overall water/urea splitting in fresh/sea water - Caihong Fang; Ran Li; Xin Wang; Fei Duan; Junfeng Lin; Yunqin Hu; Zhiqing Cui (Chemical Engineering Journal, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

DEPDC1B enhances malignant phenotypes of multiple myeloma through upregulating CCNB1 and inhibiting p53 signaling pathway - Hairong Fei; Xue Shi; Saisai Li; Ying Li; Xiangcong Yin; Zengjie Wu; Wei Wang; Hailei Shi; Ran Li (Tissue and Cell, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

A Bispecific Modeling Framework Enables the Prediction of Efficacy, Toxicity, and Optimal Molecular Design of Bispecific Antibodies Targeting MerTK - Ran Li; Edward Dere; Mandy Kwong; Mingjian Fei; Rutwij Dave; Shabkhaiz Masih; Joy Wang; Erin McNamara; Haochu Huang; Wei-Ching Liang; Leah Schutt; Amrita V. Kamath; et al. (The AAPS Journal, 2024)
Inhibiting MerTK on macrophages is a promising therapeutic strategy for augmenting anti-tumor immunity. However, blocking MerTK on retinal pigment epithelial cells (RPEs) results in retinal toxicity. Bispecific antibodies (bsAbs) containing an anti-MerTK therapeutic and anti-PD-L1 targeting arm were developed to reduce drug binding to MerTK on RPEs, since PD-L1 is overexpressed on macrophages but not RPEs. In this study, we present a modeling framework using in vitro receptor occupancy ( RO ) and pharmacokinetics (PK) data to predict efficacy, toxicity, and therapeutic index ( TI ) of anti-MerTK bsAbs. We first used simulations and in vitro RO data of anti-MerTK monospecific antibody (msAb) to estimate the required MerTK RO for in vivo efficacy and toxicity. Using these estimated RO thresholds, we employed our model to predict the efficacious and toxic doses for anti-MerTK bsAbs with varying affinities for MerTK. Our model predicted the highest TI for the anti-MerTK/PD-L1 bsAb with an attenuated MerTK binding arm, which was consistent with in vivo efficacy and toxicity observations. Subsequently, we used the model, in combination with sensitivity analysis and parameter scans, to suggest an optimal molecular design of anti-MerTK bsAb with the highest predicted TI in humans. Our prediction revealed that this optimized anti-MerTK bsAb should contain a MerTK therapeutic arm with relatively low affinity, along with a high affinity targeting arm that can bind to a low abundance target with slow turnover rate. Overall, these results demonstrated that our modeling framework can guide the rational design of bsAbs. Graphical Abstract

Effective electrosorption and recovery of phosphorus by capacitive deionization with a covalent organic framework-membrane coating electrode - Chengyi Wang; Ran Li; Yubo Xu; Zhongbao Ma; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Desalination, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Intelligent bamboo: A splendid flame retardant, fire warning and photothermal sterilization nanocoating via low-temperature evaporation induced self-assembly - Fei Yang; Qichao Bao; Chungui Du; Jiawei Zhu; Yuting Wang; Yuran Shao; Ying Ran (Chemical Engineering Journal, 2023)

Modeling China's terrestrial ecosystem gross primary productivity with BEPS model: Parameter sensitivity analysis and model calibration - Xiuli Xing; Mousong Wu; Wenxin Zhang; Weimin Ju; Torbern Tagesson; Wei He; Songhan Wang; Jun Wang; Lu Hu; Shu Yuan; Tingting Zhu; Xiaorong Wang; et al. (Agricultural and Forest Meteorology, 2023)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Association between urinary phthalate metabolites and chronic obstructive pulmonary disease incidence in US adults: results from NHANES 2007–2018 - Jiran Shen; Yue Wang; Sijing Zhou; Min Tang; Min Li; Rui Han; Guanghe Fei; Ran Wang (Environmental Science and Pollution Research, 2023)

Red mud-derived iron carbon catalyst for the removal of organic pollutants in wastewater - Yawen Fei; Ning Han; Junjie Shi; Shiyu Tang; Hezhen Zhuang; Longyu Wang; Jincheng Ran; Enxia Gao; Mohamed A. Habila; Zhijie Chen; Dongping Tao; Bing-Jie Ni; et al. (Chemosphere, 2023)

Unprecedented decline in photosynthesis caused by summer 2022 record-breaking compound drought-heatwave over Yangtze River Basin - Jun Wang; Ran Yan; Guoxiong Wu; Yimin Liu; Meirong Wang; Ning Zeng; Fei Jiang; Hengmao Wang; Wei He; Mousong Wu; Weimin Ju; Jing M. Chen (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Fluoride resistance capacity in mammalian cells involves global gene expression changes associate with ferroptosis - Yi Zhang; Yimin Fang; Shen Zhao; Jialong Wu; Chenkang Lu; Lai Jiang; Shujun Ran; Jia Wang; Fei Sun; Bin Liu (Chemico-Biological Interactions, 2023)

Observed Taylor cap around a seamount intensified by a surface mesoscale eddy in the Northwest Pacific - Yansong Liu; Qiang Ren; Fei Yu; Jianfeng Wang; Ran Wang; Feng Nan; Yanan Ding; Tongtong Zheng; Chuanzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Climate Dynamics, 2023)

Corrigendum to “Long-term environmental levels of microcystin-LR exposure induces colorectal chronic inflammation, fibrosis and barrier disruption via CSF1R/Rap1b signaling pathway” [J Hazard Mater 440 (2022) 129793] - Yue Yang; Hui Wang; Xiaoyan Wang; Ling Chen; Wenya Liu; Danping Cai; Shuxiang Deng; Hanyu Chu; Ying Liu; Xiangling Feng; Jihua Chen; Mengshi Chen; et al. (Journal of Hazardous Materials, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Interactive effects of the El Niño-Southern Oscillation and Indian Ocean Dipole on the tropical net ecosystem productivity - Ran Yan; Jun Wang; Weimin Ju; Daniel S. Goll; Atul K. Jain; Stephen Sitch; Hanqin Tian; Poulter Benjamin; Fei Jiang; Hengmao Wang (Agricultural and Forest Meteorology, 2023)

A relay of anticyclonic eddies transferring North Pacific subtropical mode water into the South China Sea - Ran Wang; Qiang Ren; Feng Nan; Fei Yu (Frontiers in Marine Science, 2023)
North Pacific subtropical mode waters (STMWs), which are subducted with air-sea interaction signals and characterized by low potential vorticity (PV), play an important role in climate change issues. STMW ( PV 2 × 10 − 10 m − 1 · s − 1 ) can be advected westward by large-scale ocean circulation and mesoscale eddies. However, whether and how the STMW intrudes into the South China Sea (SCS) remains unclear. Low PV signals that originate from the STMW and intruding into the SCS are investigated by comparing observations and ocean general circulation models during 2003-2017. These signals mostly move across the Luzon Strait (LS) into the SCS during the 2008-2009 and 2014-2016 periods. The results of case studies selected from these two periods indicate that the low PV signals can move to the LS and are trapped by anticyclonic eddies (AEs). When the velocity vorticity is negative southwest of Taiwan Island, vertical stratification becomes weaker west of the coming AE (AE1), and low PV signals can consequently be transported along the STMW layer (25.0 σ θ - 25.5 σ θ isopycnal layer). Thus, an AE (AE2) forms east of AE1 and isolates the low PV signal from AE1, and then AE2 transports the low PV water southwestward in the SCS. In contrast, the low PV signal has difficulty migrating eastward when the velocity vorticity is positive west of AE1, as vertical stratification strengthens and then weakens that signal. The results suggest that only AEs can relay low PV signals from east of the LS and carry them over long distances in the SCS.

Characteristics of a Copper-cadmium Tolerant Strain Screened from Tailings and Its Potential in Remediation of Heavy Metal Contaminated Soil - Nannan Wang; Yufan Wang; Bingbing Li; Fei Huang; Chuanhao Sun; Xintong Li; Ran Zhao; Youbao Wang (Water, Air, & Soil Pollution, 2023)

Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Qiang Ren; Yansong Liu; Ran Wang; Feng Nan; Jianfeng Wang; Xinyuan Diao; Zifei Chen; Fei Yu; Chuangzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans; however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy–Kuroshio interactions based on large-scale in situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018–2019 (12 deployed east of Taiwan within a 3 × grid) were used to reveal the three-dimensional structure of mesoscale eddies and their interaction with Kuroshio. The results show a strengthening (weakening) of the tilt of the pycnocline, which has also caused a deeper (shallower) pycnocline in eastern Taiwan following an anticyclonic (cyclonic) interaction with Kuroshio, which resulted in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downward (upward) movement at the center of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for further research on energy exchange during eddy–Kuroshio interactions.

Effects of carbonate minerals and exogenous acids on carbon flux from the chemical weathering of granite and basalt - Chaojun Li; Pete Smith; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Qin Li; Jinfeng Wang; Luhua Wu; Fei Chen; Yuanhong Deng; Zeyin Hu; Yujie Yang; et al. (Global and Planetary Change, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Superwettable Surface-Dependent efficiently electrocatalytic water splitting based on their excellent liquid adsorption and gas desorption - Fei Zhang; Ran Zhao; Yiran Wang; Lu Han; Jianmin Gu; Zhimin Niu; Yiming Yuan; Nianrui Qu; Jingxin Meng; Desong Wang (Chemical Engineering Journal, 2023)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

Therapeutic effect of the sulforaphane derivative JY4 on ulcerative colitis through the NF-κB-p65 pathway - Xiu-Juan Zhao; Yi-Ran Zhang; Wen-Fei Bai; Tong-Yan Sun; Yu-Fen Yang; Tong-Xin Wang; Cui-Gai Bai (Inflammopharmacology, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

The brassinosteroid biosynthesis gene TaD11-2A controls grain size and its elite haplotype improves wheat grain yields - Huiyuan Xu; Han Sun; Jiajin Dong; Chengxue Ma; Jingxue Li; Zhuochun Li; Yihuan Wang; Junqi Ji; Xinrong Hu; Meihui Wu; Chunhua Zhao; Ran Qin; et al. (Theoretical and Applied Genetics, 2022)

BmK DKK13, A Scorpion Toxin, Alleviates Pain Behavior in a Rat Model of Trigeminal Neuralgia by Modulating Voltage-Gated Sodium Channels and MAPKs/CREB Pathway - Ran Yang; Yongbo Song; Haipeng Wang; Chunyun Chen; Fei Bai; Chunli Li (Molecular Neurobiology, 2022)

The Physical-Biogeochemical Responses to a Subsurface Anticyclonic Eddy in the Northwest Pacific - Ya-nan Ding; Fei Yu; Qiang Ren; Feng Nan; Ran Wang; Yansong Liu; Ying Tang (Frontiers in Marine Science, 2022)
Due to the unique physical processes of mesoscale eddies, the physical and biogeochemical properties within the subsurface anticyclonic eddy (SSAE) and in the surrounding water are distinct. Analyses using satellite and model data have revealed distinct seasonal variations in the central potential density structure of a long-standing SSAE south of Japan; this SSAE exhibits a normal concave isopycnals structure from January to April and a convex lens isopycnals structure from May to December, and these variations may be related to the subduction of low-potential vorticity (PV) mode water. In contrast to the idea of the self-sustained oscillation mechanism, the strength of the SSAE was enhanced due to the eddy kinetic energy provided by dramatic increasing of the positive baroclinic conversion rate during the Kuroshio path transition period from the non-large meander (NLM) path to the large meander (LM) path. Twofold to threefold enhancement of chlorophyll (CHL) was detected in the subsurface CHL maximum layers at the core of the SSAE, and this enhancement was related to the injection of nutrients into the euphotic layer due to winter mixing and the convex of isopycnals. During the period from May to December, elevated CHL and dissolved oxygen (DO) levels and reduced nitrate levels were observed along the periphery of the eddy below the maximum subsurface CHL anomaly depth. The combined result of these two processes: (1) the central downward displaced isopycnals caused by intensified SSAE, and (2) winter mixing deepened to the nutricline due to the thickened mixed layer depth (MLD) and weakened stratification in winter 2017 (during the NLM period) may have led to numerous nutrients and CHL enrichments throughout the mixed layer, thus generating a CHL bloom in the following April. The SSAE intensified in winter 2018 (during the LM period), whereas the shallower MLD and stronger stratification limited the depth of CHL downward displacement.

Roles of Iron Limitation in Phytoplankton Dynamics in the Western and Eastern Subarctic Pacific - Hao-Ran Zhang; Yuntao Wang; Peng Xiu; Yiquan Qi; Fei Chai (Frontiers in Marine Science, 2021)
The subarctic Pacific is one of the major high-nitrate, low-chlorophyll (HNLC) regions where marine productivity is greatly limited by the supply of iron (Fe) in the region. There is a distinct seasonal difference in the chlorophyll concentrations of the east and west sides of the subarctic Pacific because of the differences in their driving mechanisms. In the western subarctic Pacific, two chlorophyll concentration peaks occur: the peak in spring and early summer is dominated by diatoms, while the peak in late summer and autumn is dominated by small phytoplankton. In the eastern subarctic Pacific, a single chlorophyll concentration peak occurs in late summer, while small phytoplankton dominate throughout the year. In this study, two one-dimensional (1D) physical–biological models with Fe cycles were applied to Ocean Station K2 (Stn. K2) in the western subarctic Pacific and Ocean Station Papa (Stn. Papa) in the eastern subarctic Pacific. These models were used to study the role of Fe limitation in regulating the seasonal differences in phytoplankton populations by reproducing the seasonal variability in ocean properties in each region. The results were reasonably comparable with observational data, i.e., cruise and Biogeochemical-Argo data, showing that the difference in bioavailable Fe (BFe) between Stn. K2 and Stn. Papa played a dominant role in controlling the respective seasonal variabilities of diatom and small phytoplankton growth. At Stn. Papa, there was less BFe, and the Fe limitation of diatom growth was two times as strong as that at Stn. K2; however, the difference in the Fe limitation of small phytoplankton growth between these two regions was relatively small. At Stn. K2, the decrease in BFe during summer reduced the growth rate of diatoms, which led to a rapid reduction in diatom biomass. Simultaneously, the decrease in BFe had little impact on small phytoplankton growth, which helped maintain the relatively high small phytoplankton biomass until autumn. The experiments that stimulated a further increase in atmospheric Fe deposition also showed that the responses of phytoplankton primary production in the eastern subarctic Pacific were stronger than those in the western subarctic Pacific but contributed little to primary production, as the Fe limitation of phytoplankton growth was replaced by macronutrient limitation.

Screening beneficial bacteriostatic lactic acid bacteria in the intestine and studies of bacteriostatic substances - Zhijing Liu; Cong Xu; Ran Tian; Wan Wang; Jiage Ma; Liya Gu; Fei Liu; Zhanmei Jiang; Juncai Hou (Journal of Zhejiang University-SCIENCE B, 2021)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Heavy metal contamination in surface sediments from lakes and their surrounding topsoils of China - Minghao Wang; Xiaoyang Liu; Bing Yang; Yang Fei; Jingjing Yu; Ran An; Lijie Duan (Environmental Science and Pollution Research, 2021)

Ecological thresholds of phytoplankton community across environmental gradients in the harmful algal blooms-frequently-occurring, subtropical coastal waters, East China Sea - Ran Ye; Chunying Ge; Qiong Wang; Qing Xu; Guofeng Xu; Yongkang Yan; Mingli Qin; Yanhong Cai; Yuejun Fei (Acta Oceanologica Sinica, 2021)

Apple MdSAT1 encodes a bHLHm1 transcription factor involved in salinity and drought responses - Yu-Ying Yang; Peng-Fei Zheng; Yi-Ran Ren; Yu-Xin Yao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Planta, 2021)

New insights into the mechanism of storage protein biosynthesis in wheat caryopsis under different nitrogen levels - Xurun Yu; Leilei Wang; Liping Ran; Xinyu Chen; Jieyue Sheng; Yang Yang; Yunfei Wu; Gang Chen; Fei Xiong (Protoplasma, 2020)

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

Cloning and functional identification of a strigolactone receptor gene MdD14 in apple - Yu-Ying Yang; Yi-Ran Ren; Peng-Fei Zheng; Ling-Ling Zhao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

PPPDE1 promotes hepatocellular carcinoma development by negatively regulate p53 and apoptosis - Xingwang Xie; Xueyan Wang; Weijia Liao; Ran Fei; Nan Wu; Xu Cong; Qian Chen; Lai Wei; Yu Wang; Hongsong Chen (Apoptosis, 2019)

Apple MdMYC2 reduces aluminum stress tolerance by directly regulating MdERF3 gene - Jian-Ping An; Xiao-Na Wang; Ji-Fang Yao; Yi-Ran Ren; Chun-Xiang You; Xiao -Fei Wang; Yu-Jin Hao (Plant and Soil, 2017)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Soil microbial community composition and its driving factors in alpine grasslands along a mountain elevational gradient - Hai-jun Cui; Gen-xu Wang; Yan Yang; Yang Yang; Rui-ying Chang; Fei Ran (Journal of Mountain Science, 2016)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

In vitro interactions between rat bone marrow-derived endothelial progenitor cells and hepatic stellate cells - Feng Liu; Zhi-da Liu; Nan Wu; Jiang-Hua Wang; Heng-Hui Zhang; Ran Fei; Xu Cong; Hong-song Chen; Lai Wei (In Vitro Cellular & Developmental Biology - Animal, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Construction of a recombinant BHV-1 expressing the VP1 gene of foot and mouth disease virus and its immunogenicity in a rabbit model - Xian-Gang Ren; Fei Xue; Yuan-Mao Zhu; Guang-Zhi Tong; Yan-Hui Wang; Jun-Ke Feng; Hong-Fei Shi; Yu-Ran Gao (Biotechnology Letters, 2009)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)

Characterization of nitrifying bacteria communities of soils from different ecological regions of China by molecular and conventional methods - Fei Yuan; Wei Ran; Qirong Shen; Dezhi Wang (Biology and Fertility of Soils, 2005)